EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISIONS) DENGAN BERBANTUAN MEDIA PERMAINAN LUDO MATH TERHADAP HASIL BELAJAR MATEMATIKA MATERI BILANGAN BULAT PADA PESERTA DIDIK KELAS IV SD GMIT WOLWAL - Herlina Karma; Imanuel Y.H. Manapa; Nehemia Fanpada (CV. Adiba Aisha Amira, 2026)
This study aimed to determine the effectiveness of the STAD cooperative learning model assisted by Ludo Math game media on students' mathematics learning outcomes. The study used a quantitative pre-experimental method with a one-group pretest-posttest design. The sample consisted of 18 fourth-grade students of SD GMIT Wolwal. The results indicated that the implementation of STAD assisted by Ludo Math improved students' learning outcomes. Hypothesis testing showed that tcount (827.043) was greater than ttable (0.213), indicating that the learning model was effective in improving mathematics achievement.